2021
DOI: 10.3390/molecules26216633
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Biological Assessment of Antidiabetic α-Mangostin Loaded Nanosponges: In Vitro, In Vivo, and In Silico Studies

Abstract: Type 2 diabetes mellitus has been a major health issue with increasing morbidity and mortality due to macrovascular and microvascular complications. The urgent need for improved methods to control hyperglycemic complications reiterates the development of innovative preventive and therapeutic treatment strategies. In this perspective, xanthone compounds in the pericarp of the mangosteen fruit, especially α-mangostin (MGN), have been recognized to restore damaged pancreatic β-cells for optimal insulin release. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…With 0.05 µM α-glucosidase and 2 mM pNPG, the IC 50 of α-mangostin was 31.1 µM (pIC 50 = 4.51 ± 0.04), showing a higher affinity than acarbose, IC 50 = 1712 µM (pIC 50 = 2.77±0.04), tested as a positive control, resulting in an inhibitory potency ratio of 55. Other authors reported the α-mangostin inhibition on α-glucosidase, showing IC 50 values ranging from 1.3 to 29.3 µM [11][12][13]33,34]; among these investigations, only three compared the inhibition with that of acarbose, evidencing a potency ratio of 2.1, 8.2 and 18.8 [11,13,34].…”
Section: α-Mangostin and Synthetic Compounds Cs1-cs4: Antioxidant Act...mentioning
confidence: 97%
See 1 more Smart Citation
“…With 0.05 µM α-glucosidase and 2 mM pNPG, the IC 50 of α-mangostin was 31.1 µM (pIC 50 = 4.51 ± 0.04), showing a higher affinity than acarbose, IC 50 = 1712 µM (pIC 50 = 2.77±0.04), tested as a positive control, resulting in an inhibitory potency ratio of 55. Other authors reported the α-mangostin inhibition on α-glucosidase, showing IC 50 values ranging from 1.3 to 29.3 µM [11][12][13]33,34]; among these investigations, only three compared the inhibition with that of acarbose, evidencing a potency ratio of 2.1, 8.2 and 18.8 [11,13,34].…”
Section: α-Mangostin and Synthetic Compounds Cs1-cs4: Antioxidant Act...mentioning
confidence: 97%
“…α-Mangostin is a 9H-xanthene-9-one derivative mainly isolated from the fruit of Garcinia mangostana L. (Clusiaceae family), commonly known as mangosteen, a plant widely cultivated in Southeast Asian countries [8][9][10]. Studies have shown that the plant-derived α-mangostin possesses several pharmacological properties, including anti-inflammatory, antidiabetic, cardioprotective, and antimicrobial activities [10][11][12][13][14]. α-Mangostin and related xanthones are generally considered safe and well tolerated in vivo [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Various physicochemical properties, including the zeta potential, entrapment efficiency, hydrodynamic diameter, and drug-release properties were also tested. The in vitro α -glucosidase inhibition potential demonstrated appreciable results, which were reinforced with in vivo studies [ 7 ].…”
mentioning
confidence: 88%
“…Furthermore, various metabolic disorders are associated with the reduction of soluble NRP-1(sNRP-1), which has protective effects against AngII-induced inflammation [ 112 , 113 ]. In addition, sNRP-1 is up-regulated in HIV-positive pregnant women due to mimicry with VEGF or integrin, which mediate angiogenesis via NRP-1 receptors [ 114 ].…”
Section: Role Of Neuropilin-1 In Covid-19mentioning
confidence: 99%